Measuring the Value of Rent Stabilization and Understanding its Implications for Racial Inequality: Evidence from New York City - Ruoyu Chen; Hanchen Jiang; Luis E. Quintero (Global Labor Organization (GLO), 2022)
Assessing rent discounts implied by rent regulation is challenging because the counterfac- tual rents of regulated units in the unregulated market are not observed. We estimate these counterfactual rents and predict the quality-adjusted rent discount for each rent-stabilized unit in New York City (NYC) using novel data from 2002 to 2017. We find robust average rent discounts of 410 per month (34% of contract rents of stabilized units). The aggregate size of these discounts in NYC is between 4 to 5.4 billion USD per year, roughly 10-14% of the federal budget on means-tested housing programs. We document that discounts: (1) increase linearly with housing tenure; (2) are not progressively distributed; (3) are larger in Manhattan and increasing in gentrifying neighborhoods; and (4) are three times larger for households correctly aware of being beneficiaries. We find that rent stabilization has disproportionately benefited White tenants. Not only are they more likely to occupy rent-stabilized units conditional on observables, but they also receive higher discounts. On average, Black stabilized tenants get 150, Hispanics 135, and AAPI 43 less on monthly rent discounts than White stabilized ten- ants. This racial gap, which has shrunk over time, is mainly explained by the uneven sorting of households of different races across locations.
Keywords: R28; J15; H75; L51; 330; Rent Stabilization; Rent Regulation; Hedonic Pricing; Policy Incidence; Racial Inequality